Exploring the effectiveness of export assistance programs on Malaysian SMEs - Hashim, Mohd Khairuddin; Zakaria, Mustafa; Ahmad, Sa'ari (Universiti Utara Malaysia Press, 2005)

(untitled)
This article reports a research that focused on export assistance programs. More specifically, the study attempted to evaluate the effectiveness of 38 export assistance programs offered to Malaysian small and medium-sized enterprises (SMEs). The data for the study was collected from 76 SMEs in the manufacturing sector. The findings of the study indicated that the SMEs were not only aware of the programs, but they also found the export assistance programs to be helpful, and that they had benefited from using the programs.